Evaluating knowledge creation processes in the Royal Malaysian Navy (RMN) fleet: Personnel conceptualization, participation and differences - Shaftdean Lufty Rusland; Noor Ismawati Jaafar; Bambang Sumintono (Cogent Business & Management, 2020)
This article analyses the Royal Malaysian Navy (RMN) fleet personnel's responses to survey questionnaire items on the knowledge creation processes, in order to identify the current extent of processes within the fleet. Through knowledge creation, new knowledge is created, starting with the discovery of knowledge and eventually, new and additional knowledge creation. Saving this created knowledge from dissipating is crucial to remain relevant. Hence, a survey was conducted on 214 of the fleet's personnel utilizing the Knowledge Creation Process SECI Model. The results revealed that knowledge creation processes are being practised in the fleet. However, the extent varied and most of the RMN fleet personnel participated at a moderate level in the processes. Socialization and internalization process dimensions are more actively utilized than externalization and combination process dimensions in knowledge creation within the fleet. Respondents with different demographic profiles had differences in their opinions, perceptions, and attitudes towards the knowledge creation processes. This needs to be looked into further since a sophisticated fleet with state-of-the-art inventories worth billions has many stakeholders concerned with safeguarding the sovereignty of the nation's maritime interests. Therefore, this study is the foundation to assist the organization to assess issues and differences related to knowledge creation in order to improve organization performance.
Keywords: 650; knowledge creation; SECI; Royal Malaysian Navy; Rasch Model; tacit knowledge; explicit knowledge